Faktor-faktor yang Berhubungan dengan Kejadian Berat Badan Lahir Rendah (BBLR) di RSUD Siti Fatimah Provinsi Sumatera Selatan Tahun 2023 - Octarine, Imelda; Hamid, Siti Aisyah; Sari, Erma Puspita (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to determine the relationship between age, anemia status and parity with the incidence of low birth weight at RSUD Siti Fatimah, South Sumatra Province in 2023. The research method used in this study is quantitative research using an analytical survey with a cross-sectional approach with a population of 1,419 people, a sample of 93 using the random sampling method. The results of this study revealed that there was a significant relationship between the frequency of age and anemia with the incidence of LBW in newborns at RSUD Siti Fatimah, South Sumatra Province in 2023